Highly sensitive and selective non-enzymatic glucose detection based on indigo carmine/hemin/H2O2 chemiluminescence. Issue 3 (17th December 2019) - Fereja, Tadesse Haile; Kitte, Shimeles Addisu; Zafar, Muhammad Nadeem; Halawa, Mohamed Ibrahim; Han, Shuang; Zhang, Wei; Xu, Guobao
Abstract : Chemiluminescence of indigo carmine/glucose/hemin/H2 O2 has been reported for the first time, and used for sensitive non-enzymatic detection of glucose and indigo carmine. Abstract : A new chemiluminescence (CL) system, indigo carmine/glucose/hemin/H2 O2, has been found and developed for non-enzymatic detection of indigo carmine (IC) and glucose. The CL response increases linearly with IC concentrations from 3.2 μM to 10 mM and glucose concentrations from 0.06 μM to 3.5 mM. The detection limits are 1.45 μM and 15.0 nM for IC and glucose, respectively. This method allows the determination of glucose in blood and urine after simple dilution. The recoveries for the determination of glucose are between 98.5% and 101.0% in blood and between 98.5% and 101.3% in urine. This method shows good sensitivity, selectivity, simplicity, and is low cost, suggesting its promising broad applications.